Anthrax: clinical investigation in the Peruvian Andes - SALINAS, DAVID (2004)
Objective: To describe the clinical characteristics of anthrax infection in patients from this town. Material and Methods: Twenty-nine suspect cases of cutaneous anthrax from Santiago de Chocorvos were studied. Cutaneous lesions had histopathology study in eleven patients with a clinical diagnosis of anthrax, along with Gram-stained smears study in six of these patients. Results: All patients presented a limited cutaneous infection. Disease started with a macule associated with itching or parestesia, that progressed to papule and ulcer. The bottom of the ulcer covered with a yellowish eschar that later became dark. An image that suggested B. anthracis was identified in a patient’s Gram stain smear. Conclusions: Anthrax is a disease that may occur at high altitude areas. Clinical characteristics of high altitude anthrax are similar to those described at the scientific literature.